The issues discussed in Friday khutbah in Malaysia an analysis study of the khutbah texts prepared by JAKIM in the year 2012 - Ibrahim, Siti Munirah; Fouad Bounama, Fouad; Muhamad Shukri, Abdul Salam (Al-Madinah International University (Malaysia), 2017)
This study aims to objectively analyze one year's worth of Friday Khutbah texts prepared by JAKIM in 2012, in an endeavor to study the nature content in terms of its titles, topics, issues covered; to discover their relevance, strengths and weaknesses. Since, presently, the Friday Khutbah in Malaysia is facing many challenges and obstacles, in terms of the topics and issues covered, and the relevance of the contents for society, whether they can reflect with the changing needs of the society or not. It is vital that the Khutbah texts should be analyzed, since Friday Khutbah has a great role in enlightening the Muslim Ummah, as well as unifying them in their stand over the challenges facing them, it has effective influences and important role in changing the thoughts in our society in all walks of life. This study is particularly based on text analysis of the texts of Khutbah and reading materials on the topic. The study uses qualitative research which basically involves the tools of library research to obtain the necessary and required data. Furthermore, in analyzing the texts of Khutbah, the study uses analytical and critical methods. The study found that the Friday Khutbah texts prepared by JAKIM were calendar based and standardized in nature. However, they were mainly focused on Muslims‟ practical life and emphasised on the basics of Islamic belief and the most known issues. Almost all the Khutbah regardless of their topic emphasised on reminding the audience about proper Islamic behaviour. However, there were some irrelevance and weaknesses found in the Khutbah texts.